Role of FEF25-75 in managing children with newly-diagnosed asthma in clinical practice - Ciprandi, Giorgio; Tosca, Maria Angela; Schiavetti, Irene; Olcese, Roberta; Miraglia del Giudice, Michele (Acta Biomedica Atenei Parmensis, 2022)
Background Reversible bronchial obstruction characterizes asthma. Spirometry is the gold standard to assess airflow, and FEV1 is the most reliable parameter in this regard. However, many children with asthma have FEV1 within the normal range despite uncontrolled asthma and worsening. Therefore, FEF25-75 has been proposed as a valuable marker of early airflow impairment. This study aimed at investigating FEF25-75 in a cohort of children with newly diagnosed asthma.Methods 381 children (122 females, mean age 11.6 years) were consecutively visited and had a new asthma diagnosis. In addition, Spirometry, type-2 phenotyping, asthma control assessment, and ACT were performed.Results 72 (18.9%) asthmatic children had impaired FEF25-75, such as